Optimizing probiotic concentrations and application techniques to reduce vibro count in rotifer techniques to rotifer (Brachionus rotundiformis) culture. - Alfaro, Connie
Aquaculture diseases brought on by the pathogenic bacteria Vibrio is one of the major hindrances to its efficient production, development, and continued growth. To combat this problem, the application of probiotics in aquaculture and its effects on suppressing and reducing Vibrio has been recognized worldwide. In this study, the Vibrio count in rotifers (Brachionus rotundiformis) was quantified and compared after being subjected to different probiotic treatments namely, the control with algal paste alone, 109 probiotic concentration mixed with algal paste, 106 probiotic concentration mixed with algal paste, and 103 probiotic concentration mixed with algal paste. Moreover, two different methods of application of the treatments were tested, which were applied during the enrichment and during the batch culture. It was found that the best probiotic concentration applied during the batch culture method that could effectively reduce Vibrio count in rotifer culture was the 106 probiotic concentration mixed with algal paste with a mean standard error of 5.00±0.00 in the inoculation method of culture. It was then followed by the 103 probiotic concentration and followed by the 109. The control group, which was algal paste alone, had significantly higher number of colonies compared to the different probiotic treatments. Between the two methods of rotifer culture, the inoculation of probiotics during the batch culture of rotifer resulted to higher Vibrio count, with the presence of both the yellow and green colony-forming Vibrio. Whereas the application of probiotics during the enrichment method in the rotifer culture resulted to lower Vibrio count, wherein only the yellow colony-forming Vibrio was found, with the best probiotic concentration of 103. In conclusion, the probiotic concentration and application method of probiotics in rotifers have a significant effect on the Vibrio count found in the rotifer culture.